Populism: What Is and Why We Need A Multidimensional Approach to Understand it - Giraudi, Giorgio C.S. (European Scientific Journal, ESJ, 2018)
Populism is the ’new big thing’ in western politics. On both sides of the Atlantic Ocean, populist leaders, movements and parties are obtaining a growing political consent. Staring from this empirical evidence, the article reconstructs the three main strands that constitute the scientific reflexion on populism showing the limits that every single strand have and proposing a new definition of populism based on a multidimensional and syncretic approach that can account for the complexity of the normative common roots that link populism to democratic theory.